136 A SHOCKING CASE OF MYOCARDITIS?. (15th December 2022) - Agbariah, Andrea; Nannelli, Chiara; Ruzzarin, Alessandro; Manfrin, Massimiliano; Donazzan, Luca; Milewski, Priscilla; Comunello, Andrea; Cemin, Roberto
Abstract: Background: Cardiac involvement is common in systemic sclerosis (SSc), being a poor prognostic factor and the leading cause of mortality. Cardiac involvement ranges from a serendipitous diagnosis to relevant cardiac manifestations such as arrhythmias, pericardial effusion, myocardial dysfunction, and valvular diseases. Case report: A 39-year-old female without remarkable medical history, on estroprogestinic therapy was admitted to our hospital in June 2020 after an out-of-hospital cardiovascular arrest due to ventricular fibrillation (VF). A coronary angiography ruled out coronary artery disease. Magnetic resonance imaging (MRI) showed a picture of acute myopericarditis characterized by late linear and nodular intramyocardial and subepicardial gadolinium enhancement of the septal and inferior segments of the left ventricle, with trivial oedema in the same location in turbo inversion recovery magnitude (TIRM) sequences. A subcutaneous-implantable cardiac defibrillator (S-ICD) was positioned for secondary prevention. At the 5 months ICD interrogation, 3 episodes of VF detected and treated by the device were documented. In December 2020 two more appropriate device interventions on polymorphic VT/VF occurred. A septal myocardial biopsy was then performed showing diffused replacement fibrosis in the absence of signs of acute inflammation or virus on the molecular investigation. In March 2021 the patient was referred to our institution after experiencing several ventricular arrhythmia episodes successfully treated by the ICD. A myocardial positron emission tomography (PET) scan documented the uptake of 18-fluorodeoxyglucose at middle and basal septum. A 'targeted' myocardial biopsy showed a substitutive fibroadiposis with sporadic inflammatory cells, in absence of cardiotropic viruses on the molecular investigation. We then initiated Anakinra, an anti-IL1 agent with an anti-inflammatory effect to prevent further development of "inflammation-driven fibrosis". Given the Raynaud's phenomenon reported by the patient, a capillaroscopy was performed, confirming isolated megacapillaries and apical haemorrhages, compatible with early pattern scleroderma. Immunologic examinations found homogeneous ANA 1:320 and anti-RNA polymerase III, while other autoantibodies, viral serologies and tubercular analysis were negative. In October 2021, the patient was readmitted to our hospital for recurrence of arrhythmic storm. A radiofrequency catheter-based ablation was performed. After a new episode of VT properly treated by the S-ICD in May 2022, the device was explanted, and a cardiac resynchronization therapy defibrillator was implanted. The genetic analysis identified a heterozygous deletion (c1262_1263del) of Lamin A (LMNA) classified as probably pathogenic in left ventricular arrhythmogenic cardiomyopathy or dilated cardiomyopathy. Conclusion: A diagnosis of borderline myocarditis in anti-RNA-polymerase III+ systemic sclerosis with heterozygous deletion of LMNA was finally formulated, after having excluded pulmonary (PET, forced vital capacity, and CO lung diffusion in normal range), cutaneous, musculoskeletal and gastro-oesophageal involvement as well as a paraneoplastic nature (by total body PET) given the positivity for antiRNA-polymerase III.